ENT 530 Social Media Portfolio: Wawaascarves / NorSyafiqah Mohd Saat - Mohd Saat, NorSyafiqah (2021)
This business is based on a sole proprietorship. Wawaascarves is located at Lot 1680, Batu 3, Lorong Salak, Kg Telok Menegon, Seksyen 36, 40470, Shah Alam. Wawaascarves Enterprise was established on 1st July 2017.Wawaascarves is a business that is categorized in apparel and clothing. It has their own mission and vision to provide a good quality product with an affordable price that is different from the others and hoping to expand the business in the near future. The product is basically targeted to a woman. Wawaascraves offer three types of materials fabrics which is cotton, chiffon and also satin. All of these fabrics are from high quality and comfortable to use and also have their own benefit. Wawaascarves product consist of Satin Shawl, Printed Cotton Shawl, Marvin Collection Printed Cotton Shawl, Camellia Pleated Shawl and Leopard Series. The price is up from RM16 to RM25 based on the type material use. Wawaascarves also often doing a promotion on a specific date to attract more customers to purchased their product and also give their customer free gift such as gift box, scrunchies and others. Student are required to create a platform such as Facebook page and have to post teaser, hard sell and soft sell. All of these are the requirements needed to ensure that student follow the rubric given by lecturer. At the end of this report, there are proofs that the student followed the criteria needed in order to fulfil the objectives of this report.